Permodelan Air Terjun Pada Rancang Bangun Panduan Lalu Lintas Berbasis Android: Waterfall Modeling In Android-Based Traffic Guide Design - Rosmiati, Rosmiati; Hendartie, Susi; Nugroho, Bayu Pratama; Sam'ani, Sam'ani; Rudini, Rudini; Badriansyah, Badriansyah (Jurnal Sains Komputer dan Teknologi Informasi, 2023)
This Android Mobile Based Traffic Guide Application is an application that can help make it easier for the public to get information about knowledge and understanding of traffic signs and criminal provisions in traffic, which can be used anywhere, anytime, and is more practical. Apart from providing the public with an understanding of traffic signs and related criminal provisions, the public can also reduce the rate of accidents that cause fatalities. This application runs on the Android platform using SQLite as a database. Users only need to see how to use the application to run it. In this application system process, the Unified Modeling Language (UML) diagram is used which refers to the waterfall model SDLC (System Development Life Cycle) system development life cycle. The results of everything that has been carried out will form an Android mobile application that will be used by all people who need it